Structural basis for lysophosphatidic acid recognition and atypical Gα q coupling by LPAR5 - Xin Li; Kai Wang; Zhongliang Xing; Min Zhang; Wen Hu; Qingning Yuan; H. Eric Xu; Li-Hua Zhao (Proceedings of the National Academy of Sciences, 2026)
Lysophosphatidic acid receptor 5 (LPAR5) is a non-endothelial differentiation gene class A G protein–coupled receptor that regulates neuropathic pain, itch, and cancer progression through coupling to G proteins. Here, we report the cryo-EM structure of LPAR5 bound to 1-oleoyl-lysophosphatidic acid (LPA) in complex with G q at 2.96 Å resolution, revealing a distinct mode of receptor activation and G protein coupling. The phosphate headgroup of LPA forms extensive polar interactions with residues from extracellular loop 2 and transmembrane helices TM5–TM7, while the lipid tail inserts into a deep hydrophobic cavity formed by TM3–TM5. Site-directed mutagenesis confirms the functional importance of these interactions. Remarkably, LPAR5 exhibits a noncanonical G protein coupling mode. Unlike previously reported GPCR–G protein structures in which the Gα C-terminal α5 helix (“wavy hook”) primarily engages TM6, the wavy hook in LPAR5 is positioned toward the intracellular loop 1–helix 8 interface. This configuration is associated with limited TM6 outward displacement and modest rearrangement at the toggle-switch position (6.48). The resulting interface is stabilized by receptor-specific interactions and supported by functional data. Together, these findings reveal an alternative mode of GPCR–G protein coupling and highlight the structural plasticity underlying signaling specificity in LPA receptors.